Managing Change in Organizations - Colin A. Carnall (Canada Pearson Education Canada, 2012)
Managing Change in Organizations provides a practical and thorough overview of how effective change can be achieved in organizations. The text is ideal for advanced undergraduates, MBA and postgraduate students on courses in managing change and organizational change. Colin Carnall takes a strategic approach, outlining guidance and techniques for planning and implementing, evaluating and learning from major organizational change. Reviewing traditional and more recent critical theories, he presents models and frameworks for change that are apt for the complex and fast-moving challenges of contemporary organizations.
Keywords: Organization; Managing change; Textbooks